The Alhambra Museum: History, Conservation and Management of its tile and tiling mosaic collections - Dias Martins, Danielle (Ge-conservacion, 2024)
The documentation of the collections is a fundamental step towards the conservation of cultural heritage. It is a complicated process that involves several phases closely related to the different stages of the artefacts in a museum: from their acquisition, registration, inventory, cataloguing, conservation, maintenance and exhibition to their communication. The information presented in this document aims firstly to provide a better understanding of the different phases of the objects in the specific context of the Alhambra Museum, in addition to comply with the communication purpose that is inherent to the knowledge and necessary for the recognition and appreciation of historical objects. The main objective of this research is to analyse the evolution of the Alhambra Museum and its collection, especially focusing on the tile and tiling mosaics that, although they are part of the most emblematic and distinctive typologies of the palatine city, have not had the chance to be available to the scientific-academic community.